(untitled) (Research, Society and Development, 2020)
The objective of this study is to evaluate the perception of education professionals, before and after the application of theoretical and practical training based on active methodologies, on safety and prevention against fire and evacuation in disaster situations. The research method adopted is action research, as it involves diagnosis, planning, action and evaluation to identify the perception of fire protection education professionals. The population consists of 29 education professionals and 75 students, aged between 4 and 5 years, from a private school in the city of Itabira-MG. The structured questionnaire technique is used for teachers and employees, applied before the project to measure the interviewees ’prior knowledge and after the project, to evaluate the effectiveness of the applied training, the teachers’ perception of their and children’s learning and the need for the topic to be an issue that the school community should constantly address as an important issue in the school calendar schedule. The results indicate that it is necessary to adopt safety training in schools and to keep this training constant. It is concluded that if teachers and school staff undergo regular training they will be able to act consciously, with students, in an emergency. That it is important to use scientific methods so that a broad and effective learning occurs and it is necessary to adopt the theme in the syllabus of schools.